Liberty, property and the state: The ideology of the institution of English town and country planning. (January 2020) - Shepherd, Edward
Highlights: Explores the relationship between shifts in national political ideologies and institutional changes in English town and country planning. Argues that the institution of national English town and country planning is connected with concepts which are prone to ideological contestation. Examines how shifts in the meanings of these concepts relate to changes in, but also the stability of, the institution of English planning. Explores how inconsistency and incoherence are necessary qualities of both ideology and planning. Abstract: The research explores the relationship between national political ideologies and policy and legislative changes in national English town and country planning. English national planning policy making is theorised as being partly driven by ideological contestation. The research contributes to the understanding of the nature of the policies this process produces, and how it is that the English planning system has become a 'wicked problem' for national policy makers. The analysis focuses on two periods: the '1947 system' period and the early post-2010 Conservative-led Coalition government period. The '1947 system' period has been selected as it is a key phase in the institutionalisation of English town and country planning into a formal institution of the state. The early Coalition government period has been chosen for analysis as it is the most recent period of significant institutional change. Both of these periods are contextualised through a discussion of developments in politics and planning in the preceding decades. The research shows that the institution of national English town and country planning is intimately connected with concepts which are deeply prone to ideological contestation (such as liberty, property and the state), and that these competing contestations influence competing visions for the form and structure of the institution. This ideological quality of 'thinking about planning' means that its institutionalised form is inherently prone to change. The research proposes a theory for the analysis of ideology and ideas as they relate to institutional change, and offers an account of the power of ideology to define the limits of politically acceptable thought, and thus shape policy and legislative programmes for English planning. The contribution of this research is towards an understanding of why ideologies have shaped the institution of national English town and country planning over time.